Electoral behavior in Sarawak : the Lun Bawang and issue-voting / Chai Shin Yi ... [et al.] - Yi, Chai Shin; Yusuf, Nur Afisha; Sadikin, Sarehan; Jugah, Ivy; Liwi, Christina; Nheru, Darien Sigie (Universiti Teknologi MARA, Shah Alam, 2019)
This study aims to determine Lun Bawang voters’ opinion on issues that would influence their vote in Bakelalan (N.81), Sarawak. A survey was conducted in the village of Kampung Puneng Berayong, located in the Lawas P.222 parliamentary constituent. A five-point Likert scale questionnaire was distributed to 250 Lun Bawang voters. The questionnaire highlighted key issues on development, NCR land, and good governance. It is assumed that rural voters tend to vote based on the rational choice approach which meant they would consider what benefits could be gained by supporting a particular candidate or political party. It was found that local electoral issues such as development and native customary rights (NCR) land were more favored compared to national issues on corruption such the 1MDB case.